Response of Chemical Fertilizers on Eucalyptus tereticornis Clones - Kumari, T. Kusuma; Sreenivasulu, A.; Meru, Elusing; Rao, P. S. (Indian Forester, 2002)
The field experiment on response to fertilizers on clones of Eucalyptus tereticornis in forest land of Tirupati , Andhra Pradesh , India revealed that interaction of N , P and K@60 kg of N/ha , 90 kg of P2O5/ha and 60 kg of K2O/ha were most significant on growth parameters than individual effects of N , P and K.